2011
DOI: 10.1124/jpet.111.184788
|View full text |Cite
|
Sign up to set email alerts
|

Umami Receptor Activation Increases Duodenal Bicarbonate Secretion via Glucagon-Like Peptide-2 Release in Rats

Abstract: Luminal nutrient chemosensing during meal ingestion is mediated by intestinal endocrine cells, which regulate secretion and motility via the release of gut hormones. We have reported that luminal coperfusion of L-Glu and IMP, common condiments providing the umami or proteinaceous taste, synergistically increases duodenal bicarbonate secretion (DBS) possibly via taste receptor heterodimers, taste receptor type 1, member 1 (T1R1)/R3. We hypothesized that glucose-dependent insulinotropic peptide (GIP) or glucagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 42 publications
9
63
0
Order By: Relevance
“…This suggests that modification of colonic motility can be achieved by physiological amino acids in the gut. Previous studies in the proximal gut show that certain L-AAs can cause activation of T1R1/T1R3 specifically, while other L-AAs may affect different amino acid-sensing receptors (10,29,43,44). We have shown the effect of activation of the L-AA-sensing T1R1/T1R3 on motility of the distal colon.…”
Section: Discussionmentioning
confidence: 73%
“…This suggests that modification of colonic motility can be achieved by physiological amino acids in the gut. Previous studies in the proximal gut show that certain L-AAs can cause activation of T1R1/T1R3 specifically, while other L-AAs may affect different amino acid-sensing receptors (10,29,43,44). We have shown the effect of activation of the L-AA-sensing T1R1/T1R3 on motility of the distal colon.…”
Section: Discussionmentioning
confidence: 73%
“…Since luminal nutrients, including fatty acids, stimulate the production and secretion of GLP-2 in the intestinal mucosa, a HFD may contribute to intestinal tumorigenesis via increased mucosal GLP-2 (33,34). Chronic exposure to a HFD significantly increases the concentration of plasma GLP-2 and intestinal crypt-villus height (35).…”
Section: Discussionmentioning
confidence: 99%
“…Although the direct effects of GLP-2 on liver and lung health of livestock have not been evaluated, feeding of aspartate for 20 d to weanling pigs was shown to affect mRNA expression of proinflammatory signaling molecules in the toll-like receptor 4 and nuclear-binding and oligomerization domain pathways that modulate innate and adaptive immune function, and to improve serum indicators of liver damage after an intraperitoneal LPS challenge [109]. Although the mechanism of action of aspartate supplementation and plasma GLP-2 level were not evaluated in their study, feeding of this amino acid has the potential to promote GLP-2 release from intestinal L cells [100,101] through activation of taste receptors (eg, T1R1-T1R3) and could contribute to the positive hepatic effects observed. Given the potential benefits of GLP-2 on liver health, evaluation of GLP-2 for the prevention of hepatic disorders in production animals, such as fatty liver in transition dairy cows, is warranted.…”
Section: Potential Uses Of Glp-2 and Stimulators Of Glp-2 Secretion Imentioning
confidence: 92%
“…Of interest, taste receptor T1R1-T1R3 activation by both L-glutamate and inosine 5 0 -monophosphate increases GLP-2 release in rat duodenum [100], and both GLP-2 administration and a combined treatment of L-alanine with inosine 5 0 -monophosphate increase the healing rate of intestinal ulcers in rats [47]. In addition, Bauchart-Thevret et al [101] demonstrated that dietary monosodium glutamate supplementation of preterm pigs dose-dependently increases plasma GLP-2 concentration.…”
Section: Potential Uses Of Glp-2 and Stimulators Of Glp-2 Secretion Imentioning
confidence: 97%